Clap switch smarthome / Mohd Haziq Jasni & Shahrul Saifuddin Ahmad Rosli - Jasni, Mohd Haziq; Ahmad Rosli, Shahrul Saifuddin (2015)
Clap switch is a switch which can switch on/off my electrical circuit by the sound of the clap. This design is made to make people life more easy especially for an elderly or mobility impaired person. It is also can reduce electric shock cause by the switch (they use wet hand to tum ON or OFF the lamp). People also do not need to run or waste the time just for to tum ON or OFF the lamp. They can save energy and time with this design. The basic idea of clap switch is that the electric microphone picks up the sound of your claps, coughs, and the sound of that book knocked off the table, it produces a small electrical signal which is amplified by the succeeding transistor stage. This circuit is constructed using basic electronic components like resistors, transistors, relay, transformer, capacitors. The primary application involves as elderly or mobility-impaired person. It is generally used for a light, television, radio, or similar electronic device that the person will want to tum ON or OFF from bed. The major disadvantage is that, it is generally cumbersome to have to clap one's hands to tum something ON or OFF and ifs generally seen as simpler for most use cases to use a traditional light switch